Phosphorus demand and uptake during growth and maturation of the brown alga Sargassum macrocarpum. Issue 4 (13th July 2020) - Ohtake, Masahiro; Nishihara, Gregory N.; Inoue, Yukio; Tsuchiya, Kenji; Toda, Tatsuki
SUMMARY: We investigated the monthly variations of estimated in‐situ uptake and growth‐related demand for phosphorus in Sargassum macrocarpum during a growth period from December 2017 to April 2018, a maturation period from May to August 2018, and the second‐growth period from September 2018 to January 2019. Phosphate uptake was relatively low during maturation and high during growth, and coincided with changes in external phosphate levels. The demand for phosphorus was at its highest in March 2018, which corresponded with the highest growth rate and tissue phosphorus levels. Thereafter, the demand was relatively constant between April 2018 and January 2019. Consequently, the uptake rate exceeded demand from December 2017 to February 2018 and December 2018 to January 2019, suggesting that phosphorus accumulated in tissues. Additionally, the uptake rates between March 2018 and November 2018 were 0.1–0.8 times lower than the demand, probably resulting in the effective use of stored phosphorus to sustain growth during this phosphate‐depleted period. The variations between estimated uptake and demands for P found in S. macrocarpum indicate that P dynamics vary with life stage and are implicitly linked to the season.